Transformation of land use change in Cilegon City 2017-2023 using passive sensor satellite imagery - Kurniawan, Surya; Nurhaidar, Wa Ode; Gaffara, Ghefra Rizkan (Institute of Computer Science (IOCS), 2024)
Transformation Land change that occurred in Cilegon City is a phenomenon that involves a significant transformation in urban land use over the last few years. Land is a natural resource that has an important function to meet various human needs. This change was caused by several factors, one of which was rapid population growth. This research involves analyzing satellite imagery from several different time periods to track the evolution of land use in Cilegon City. From the results of observations made, it is known that there is a reduction in green land in Cilegon City. Where in each period of the year there are changes in green land which is increasingly decreasing. This reduction was caused by several factors, namely the transfer of land function from greenland to housing and the occurrence of fires on the green land.